Is neutropenia still the main risk factor for invasive aspergillosis? A contemporary university hospital retrospective cohort of invasive aspergillosis in neutropenic and non-neutropenic patients - Andrea Gutiérrez-Villanueva; Itziar Diego-Yagüe; Isabel Gutiérrez-Martín; Sonia García-Prieto; Edith Gutiérrez-Abreu; Román Fernández-Guitián; Isabel Castilla-Martínez; Naomi Bermejo-Moreno; Nuria Miguel-Ontañon; Jorge Calderón-Parra; Alejandro Callejas-Díaz; Alberto Díaz-de Santiago; et al. (Annals of Clinical Microbiology and Antimicrobials)
Abstract Introduction In times of mold active prophylaxis, invasive aspergillosis (IA) epidemiology is evolving. Presentation in non-neutropenic may differ from neutropenic. We investigated the cases of IA in our center with a focus on differences between neutropenic and non-neutropenic, and analyzed the impact of cryptic and non-fumigatus Aspergillus species. Methods Retrospective observational study including all adult patients admitted to the Puerta de Hierro-Majadahonda Hospital between January 2018 and April 2024 with IA. Results 112 IA were identified. Only 11 (9.8%) had neutropenia as risk factor for IA. Most frequent risk factors were corticosteroids (77.2%), SOT (46.5%), SARS-CoV2 (29.7%) and CMV replication (28.7%). 89.3% were pulmonary IA with 6 cases (5.4%) of disseminated infection. A. fumigatus was the most frequent species 48 (51.6%). 13 cases (14%) were caused by cryptic Aspergillus spp. Non-neutropenic patients, compared to neutropenic patients, were more likely to have positive fungal cultures (83.2% versus 54.5%, p = 0.023[NS]), and not to present a halo sign (7.4% versus 45.5%, p = 0.003 [NS]). In addition, in non-neutropenic patients, compared to neutropenic patients, there was a trend towards a greater probability of positive GM from BAL (81.3% versus 66.7%, p = 0.304) and a trend towards a lower probability of positive serum GM (25.7% versus 45.5%, p = 0.137). 41/112 (36.6%) cases presented breakthrough IFI and in 51.2%, (21/41 cases), the isolate was resistant to the prior antifungal. One presented A. fumigatus with the TR34-L98H mutation. Conclusion Risk factors different than neutropenia are currently the most common in IA. The clinical presentation in non-neutropenic patients differs from neutropenic. Resistance to antifungals is emerging especially in breakthrough IA.